The Effect Of Dietary Supplemented Ginger And Probiotic On The Productive Performance, Nutrient Digestibility, And Blood Metabolites Of Growing Karadi Lambs - mawlood, chiya (University of Thi-Qar Journal of agricultural research, 2025)
This study aimed to assess the impact of using different amounts of ginger and probiotic in feed of Karadi lambs(%0 control,%3 ginger,%3 probiotic,%3 ginger+%3 probiotic) on productive performance ,nutrient digestibility and blood metabolites. Twenty male lambs (4-5 months old and initial weight 25±5 kg) were randomly divided into four groups (5 lambs for each group) individually penned for 84 days (12 weeks). Each group include 5 lambs as (control, T1, T2, T3).Lambs fed a concentrate diet containing 16% protein at the level of %3 of their live body weight and wheat straw was ad libitum throughout the period of the study. Control (receive basal diet), T1 (receive basal diet with 3g ginger /head/day), T2 (receive basal diet with 3g probiotic/head/day), T3 (receive basal diet with 3g ginger /head/day+ 3g probiotic/head/day). Treatment 1 experienced a higher feed intake and significant (p < 0.05) rise in body weight gain, this could be because of supplemented ginger improved nutritional absorption. The positive effect of using ginger and probiotic was observed in dry matter digestibility, organic matter digestibility, crude protein digestibility, ether extract digestibility, crude fiber digestibility, NFE digestibility, NDF digestibility and ADF digestibility comparing to control ,the result refer to ginger and probiotic addition that they improve digestion, nutrient absorption and gut health of lambs. Collections of blood samples were obtained at the final stage of research study. The overall findings regarding blood plasma measures in lambs that received different experimental diets showed that all treatments displayed little effect on the assessed parameters, as the variations attributable to treatment effects were not statistically significant (p < 0.05), with the exception of albumin and creatinine levels were significant (p < 0.05). Feeding lambs diets supplemented with the experimental additions resulted in significantly (p < 0.05) different pH values, The pH value (p < 0.05) in T3 shows an increase in the result comparing to control which is due to the combination of ginger and probiotic in the diet, while T2 has lower pH value (p < 0.05) comparing to control. In the current research, animals in the T2 group showed an increased amount of total volatile fatty acids (TVFA’s) in rumen fluid comparing to other groups. The results indicated that ruminal ammonia nitrogen concentrations were significantly (p < 0.05) lower in control group than other groups. The reduction in Ammonia (NH3-N) content in livestock diets enriched with probiotics (Direct Fed Microbial) may be attributed to enhanced assimilation of ammonia into microbial protein. T1 group receive ginger and basal diet shows the highest significant (p < 0.05) level of ammonia concentration.